Contribution of the land use allocation model for agroecosystems: The case of Torrecchia Vecchia. (15th December 2019) - Elalamy, Yanis; Doyen, Luc; Mouysset, Lauriane
Abstract: In this study, we developed a bio-economic model coupling land use and ecosystem services to investigate the role of forests on a broad set of ecosystem services, including carbon sequestration, soil quality and biodiversity. As a case study, the model was calibrated with economic, agronomic and ecological data from the Torrecchia Vecchia agroecosystem in Italy. In our analysis of optimal land use allocation, the results showed that diversified land use is required to provide a good balance between provisioning and non-provisioning ecosystem services. More specifically, the development of woodlands alongside farming activities had a positive impact on the soil quality score and on landscape heterogeneity, which is a proxy for ecosystem function and resilience. These findings demonstrate that the inclusion of woodlands can alleviate the trade-offs between provisioning and non-provisioning services as they can generate profit while allowing for better soil quality and biodiversity relative to more intensive land use. The study also confirms that a landscape-scale method can be used to investigate agroecosystem management problems when spatially explicit data is not available. Highlights: Trade-off between provisioning services and non-provisioning services. Cropland and woodland diversification for balanced provisioning/non-provisioning ES. Woodland has significant impact on key ES such as soil ES and heterogeneity. Woodlands alleviate trade-offs, generating profit while better accommodating key ES.